2013
DOI: 10.1007/s13402-013-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-429 up-regulation induces apoptosis and suppresses invasion by targeting Bcl-2 and SP-1 in esophageal carcinoma

Abstract: In primary EC tissues miR-429 is expressed at low levels. Up-regulation of miR-429 inhibits invasion and promotes apoptosis in EC cells by targeting Bcl-2 and SP1. Our findings suggest that Bcl-2 and SP1 may serve as major targets of miR-429. This study paves the way for a better understanding of the mechanism underlying EC pathogenesis and the development of novel, targeted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 39 publications
4
53
0
Order By: Relevance
“…Dual roles of miR-429 have been suggested in a variety of types of human cancer, including ovarian (12), colorectal (13)(14)(15), esophageal (16) and gastric cancer (17,18), as well as osteosarcoma (19). Yoneyama et al (20) demonstrated that the expression level of miR-429, accompanied with miR-200a/b, was significantly increased in endometrioid endometrial carcinoma (ECC) compared to adjacent normal endometrial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Dual roles of miR-429 have been suggested in a variety of types of human cancer, including ovarian (12), colorectal (13)(14)(15), esophageal (16) and gastric cancer (17,18), as well as osteosarcoma (19). Yoneyama et al (20) demonstrated that the expression level of miR-429, accompanied with miR-200a/b, was significantly increased in endometrioid endometrial carcinoma (ECC) compared to adjacent normal endometrial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…miR-145 was also found to regulate SP1 in ovarian cancer cells sensitized to paclitaxel (44). In esophageal carcinoma, Wang et al (45) found that ectopic miR-429 suppressed cell invasion and induced cell apoptosis via the blockade of SP1. Zhang et al (46) demonstrated that miR-377 decreased cell growth and invasion ability by inhibiting SP1.…”
Section: Discussionmentioning
confidence: 97%
“…Some research has estimated that miRNAs may regulate up to 30% of all human genes and control a variety of cellular processes (27)(28)(29). miRNAs have been shown to be deregulated in various cancers, and their expression levels are related with the diagnosis and prognosis of different types of tumors (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%